Microstructural and tensile properties of Fe and Bi added Sn-1Ag-0.5Cu solder alloy under high temperature environment - Ali, Bakhtiar; Sabri, Mohd Faizul Mohd; Said, Suhana Mohd; Sukiman, Nazatul Liana; Jauhari, Iswadi; Mahdavifard, Mohammad Hossein (Elsevier, 2018)
In this work, the iron (Fe) and bismuth (Bi) added (0.05 wt% Fe and 1 wt% or 2 wt% Bi) Sn-1Ag-0.5Cu (SAC105) lead-free solder alloys were prepared and their microstructure and tensile properties under severe thermal environments were extensively investigated and compared with the base alloy SAC105. The isothermal aging was done at 200 °C for 100 h, 200 h, and 300 h. Fe/Bi added SAC105 showed a significant reduction in the IMCs size (Ag3Sn and Cu6Sn5), especially the Cu6Sn5 IMCs and a refinement in the microstructure, which is due to the existence of Bi in the alloys. Moreover, the existence of Fe and Bi gives the microstructure better stability under severe thermal aging conditions. The tensile testing results showed that the addition of Fe and Bi to SAC105 greatly improves yield stress and tensile strength, but decreases ductility level, which is because of the Bi solid solution strengthening mechanism. Under severe thermal aging, the Fe/Bi added SAC105 showed more stable tensile properties, because of the existence of both Fe and Bi in the alloys.